A design approach to reduce hull weight of naval ships. Issue 2 (4th May 2022) - Aguiari, M.; Gaiotti, M.; Rizzo, C. M.
ABSTRACT: Hull weight is a design parameter affecting the whole performances of a ship, being related to building costs, operational costs, maintenance and durability, and not least to satisfaction of functional requirements. Naval ships are no exception and impact of hull weight is crucial to fulfil mission requirements. In the light of the above, weight reduction is one of the main design drivers and it should be duly accounted for since the concept design phase. In this paper, a design approach intended for pre-contractual design phases is presented. It takes advantage of recent developments and trends of construction rules as well as of nowadays-available computation potential to update and improve the traditional scantling design approach, applied since decades by designers. The complexity and computational burden is kept to a minimum to provide a user-friendly procedure applicable in everyday working practice. Designers' experience and judgment continue to drive the whole process. A Visual Basic support software has been developed with worksheet interfaces to implement the proposed scantling design procedure. Test cases showed significant weight reductions with respect to as-built ships and to scantling obtained by applying traditional design procedures.